The New Testament teaching on family matters - Osiek, Carolyn (HTS teologiese studies, 2006)
The article shows that first-century urban Christian communities, such as those founded by Paul, brought in both whole families and individual women, slaves, and others. An example of an early Christian family can be seen in the autobiographical details of the Shepherd of Hermas, whether factual or not. The article aims to demonstrate that the New Testament teaching on family gives two very different pictures: the structured harmony of the patriarchal family as presented in the household codes of Colossians 3 and Ephesians 5, over against the warnings and challenges of Jesus in the Synoptic Gospels to leave family in favor of discipleship. The developing devotion to martyrdom strengthened the appeal to denial. Another version of the essay was published in Horsley, Richard A (ed), A people’s history of Christianity, Volume 1: Christian origins, 201-220. Minneapolis, MN: Fortress.1.